The Regional assessment of the implementation of wheat flour fortification in the Eastern Mediterranean Region (International Journal of Scientific Research and Management (IJSRM), 2019)
Background: Wheat flour fortification is a preventive food-based approach aimed at reducing vitamin and mineral deficiencies or insufficiencies and their consequences. Fortification of industrially processed wheat flour, when appropriately implemented, is a simple, inexpensive and effective strategy for supplying vitamins and minerals to large segments of the world’s population. Objectives: The main objective of the study was to assess the current state of wheat flour fortification in the Eastern Mediterranean Region, identify common challenges and lessons learned from country experiences, outline the latest guidance on best practices, and make recommendations to advance appropriate wheat flour fortification in the Region. Methods: A questionnaire was designed to assess progress on the implementation of flour fortification in the Eastern Mediterranean Region according to key indicators. The questionnaire was circulated to the nutrition focal points within the Ministry of Health (MOH) in all countries of the Region. The data were extracted, analyzed and discussed in a regional Workshop organized by WHO in 2017. Data were verified or gaps were filled through other potential resources, such as MOH websites, WHO, World Bank, the Food Fortification Initiative and CDC. Results: The study shows that flour fortification has been widely used in countries of the Eastern Mediterranean Region. Most countries (17 of 22 in the Region) have some coverage of wheat flour fortified with iron and folic acid, and this is mandatory in 11 countries. Eight countries fortify flour with B-vitamins. Fortification with vitamin D, vitamin A and zinc is currently rare (two countries in each case). Quality control and monitoring of wheat flour is still a big challenge in all countries. Conclusion and recommendations: Considerable progress has been made in tackling micronutrient deficiencies, and wheat flour fortification has contributed to this. However, given that micronutrient deficiencies persist in the Region further progress is needed. Furthermore, countries need to review their policies and practices to ensure that they are in line with WHO guidance on best practice and that wheat flour fortification is being appropriately implemented.